The Effort of Principal Improving Quality Education In Online Learning at SD Muhammadiyah Blimbingrejo Jepara - Rz. Ricky Satria Wiranata; Fairuz Nurillah Khoirunnisa; Diningrum Citraningsih (Journal of Childhood Development, 2022)
This study aims to determine the principal's efforts in improving the quality of education in online learning at SD Muhammadiyah Blimbingrejo Jepara and the supporting and inhibiting factors. This study uses a qualitative approach. The research subjects were principals, vice principals and teachers. Research data obtained through interviews, observation and documentation. Data analysis techniques with data reduction, data presentation and drawing conclusions. Checking the validity of the data obtained through triangulation of sources and triangulation of techniques. The results of this study indicate that the state of education quality before the pandemic was quite good. However, the quality of education began to decline after the pandemic and the implementation of online learning. Efforts made by school principals in improving the quality of education in online learning are carrying out their functions as school principals, implementing curriculum according to needs, optimizing the procurement of online learning support devices, and controlling online learning activities. Improving the quality of education in online learning is supported by adequate school facilities, but also experiences obstacles, including the majority of teachers in schools are dominated by female teachers so that management is needed in assigning tasks and responsibilities to teachers who are able to carry it out and there are teachers who lack the ability to do it. the use of technology or digital literacy, as well as students who are bored in carrying out online learning